EFFECTS OF SERVICE QUALITY MANAGEMENT ON COMPETITIVE ADVANTAGE OF TELCOMMINICATION INDUSTRY IN MOGADISHU SOMALIA - YUSUF, HUSSEIN HASSAN; THEURI, Dr FRIDAH (IJRDO - Journal of Business Management, 2016)
The general objective of this study was to investigate the service quality management oncompetitive advantage on mobile telephone providers in Somalia with specific focus of the industrial mobileproviders in Somalia . Specifically, this study investigated the effects service quality on competitive advantageon mobile providers in Somalia . The study employed a survey research design in data collection. This researchemployed quantitative data collection method whereby data was gathered by the use of closed endedquestionnaires which were self administered. Factor analysis was used to assess the validity and Cronbach alphato assess reliability of the questionnaire. Multiple regression analysis (standard and step wise) were conductedto determine the effects between the service quality determinants and competitive advantage. Results confirmthe varying importance of service quality determinants in the telephone providers processing in Somalia. Ingeneral, the results reveal that customer loyality,price fairness and brand image have significant and positiveeffects on competitive advantage in the mobile providers in Somalia. The study recommends that to improvecustomer satisfaction in the mobile providers in Somalia , managers of the industrial mobile providers in Somaliashould nurture and develop market competition and customer satisfaction The general objective of the study isto investigate the effects service quality management on competitive advantage mobile providers in Mogadishu.Specifically, this study investigated to ascertain how customer loyalty mgt affects, price fairness affects andbrand image on competitive advantage mobile providers in Mogadishu Somalia The study employed a surveyresearch design in data collection. This research employed quantitative data collection method whereby datawas gathered by the use of closed ended questionnaires which were self administered. Factor analysis was usedto assess the validity and Cronbach alpha to assess reliability of the questionnaire. Multiple regression analysiswas performed to assess the relationship between the dependent variable (value addition) and the independentvariables (customer loyalty mgt, price fairness and brand image) and to test the research hypotheses on theservice quality mgt determinants of competitive advantage in the mobile providers in Somalia with specific focuson Mogadishu The study recommends that to improve competitive advantage in mobile industry MogadishuSomalia, managers of mobile industry Somalia in Mogadishu should nurture and develop customer loyalty andprice fairness